1966
DOI: 10.1063/1.1726760
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Theory of Chemical Kinetics : Application to Neutral-Atom—Molecule Reactions

Abstract: A theory of the cross sections of three-body gas-phase reactions which proceed without activation energy is presented. It is based on the hypothesis that the decomposition of a collision complex is governed by the phase space available to each product under conservation of angular momentum and energy. Calculations on model ion-molecule systems show that the cross section is enhanced if the reaction is exothermic, the final reduced mass is large, and the final long-range attractive forces are large. The theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
0
3

Year Published

1980
1980
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 455 publications
(145 citation statements)
references
References 23 publications
2
140
0
3
Order By: Relevance
“…Such a distribution could result if photoexcitation is followed by internal conversion to the ground-state surface, and the resulting microcanonical ensemble lives long enough for the available energy to be randomized among the vibrational modes of the molecule. To test this possibility, both the one-photon and multiphoton distributions are calculated using phase space theory (PST), 55 a reasonable statistical model to apply in the case of barrierless dissociation.…”
Section: Discussionmentioning
confidence: 99%
“…Such a distribution could result if photoexcitation is followed by internal conversion to the ground-state surface, and the resulting microcanonical ensemble lives long enough for the available energy to be randomized among the vibrational modes of the molecule. To test this possibility, both the one-photon and multiphoton distributions are calculated using phase space theory (PST), 55 a reasonable statistical model to apply in the case of barrierless dissociation.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] If this is so, the total reaction probability, in Fig. 1 open channels in the product channels, in contrast to the few channels of OH + N reactants.…”
Section: A Reaction Probabilitiesmentioning
confidence: 99%
“…The comparison between phase space [84] statistical calculations [31], experimental data and dynamical studies of the title reaction have shown that the dynamics of the OH 2 complex plays an important role on the energy distribution of the products. The higher rotational energy of the products has already been noted by Buss et al [18] and has been explained as a result of the excitation of the vibrational bending mode due to the insertion mechanism.…”
Section: Product Energy Distributionsmentioning
confidence: 99%